Globalizacija sporta(na primere futbola) - Poli, R. (Science in Olympic Sport, 2019)
Objective. To consider and analyze the globalization of the international division of labor, migration channels and the transnational professional network as exemplified in football. Results. The article discusses the problem of globalization in modern sports. The subject of the article is the consideration of the international mobility of gifted athletes, in particular football players. The article consists of three parts. The first part presents three points of view on globalization, which are adjusted using the links to studies of the migration of footballers. The second part deals with the geography of international movements of footballers and the analysis of the quantitative dynamics of the presence of foreign players in the five European leagues (English Premier League, Spanish Premier League, Italian Serie A, French 1 League and German Bundesliga). The third part examines the actual data on the activity of player movement networks. To illustrate the functional unification of leagues, three typical examples of the rising careers of African players who have won seats in the English Premier League, were used. Conclusion. The study of the migration market of footballers and the trade in football shows the urgent need for introduction of people (actors) mediation and the social inclusion of their actions as a basis for analyzing this crucial process in the modern world.